PEMANFAATAN LIMBAH PLASTIK MENJADI PRODUK KREATIF SEBAGAI MEDIA PEMBELAJARAN BAGI PELAJAR DESA TERUSAN MULYA, KABUPATEN KAPUAS, KALIMANTAN TENGAH - Muhammad Aqshadigrama; Sintya Ally Faradilla; Enrico Johanes (COVIT (Community Service of Health), 2023)
As is known, the discovery of plastic has a positive impact that helps humans a lot, because plastic has advantages over other materials. However, plastic is a component of a substance that cannot be decomposed, thus raising concerns that it will become a destructive waste, even though the number continues to increase. This can be seen from the case of increasing plastic waste that has occurred in the village of Terusan Mulya. If this problem is not resolved, it will become a serious problem. Based on this analysis, this community service activity needs to be carried out in a program that can increase public awareness, especially for students to care about protecting their environment. Therefore, the approach of making creative products or handicrafts from plastic waste management is the method chosen, because it can be a learning medium that develops students' creativity and curiosity. Based on the results of the evaluation, it is known that the practical benefits obtained by the students in the Terusan Mulya Village are: 1) the students receive clear and complete information regarding the nature of community empowerment in terms of knowledge and skills. 2) The students who participate in the training get a clear picture of the potential steps for making creative products by utilizing single-use plastic waste to sell, so it has economic value. 3) Training participants also get a clear and complete picture of the benefits of waste if it is managed properly. Keywords: Plastic Waste, Creative Products, Learning Media, Students, Mulya Canal